Increasing Knowledge of Stunting through Education for Pregnant Women in the Second and Trimester - Kartini H, Anita; Sumarmi; Nuryana, Riska; Hamka; Wulandari, Rezky (Bantayang Omni Cendekia, 2026)
Background: Stunting is a growth disorder in children under five characterized by inappropriate height-for-age (TB/U) measurements. Various preventive efforts have been implemented, including routine classes for pregnant women that provide education about stunting to improve maternal knowledge and awareness. Objective: To describe changes in the level of knowledge among primigravida pregnant women in the second and third trimester before and after receiving stunting education. Methods: This study used a one-group pretest–posttest design involving 32 primigravida pregnant women selected through purposive sampling. Knowledge was measured using a structured questionnaire administered before and after the educational intervention. Results: Prior to the intervention, only seven respondents (21.9%) demonstrated good knowledge, while twenty-five respondents (78.1%) showed poor knowledge regarding stunting. Following the educational session, the number of respondents with good knowledge increased markedly to seventeen (53.1%), while those with sufficient knowledge were fifteen (46.9%). These findings indicate a substantial improvement in knowledge after the intervention. Conclusion: Educational intervention effectively increased the knowledge of pregnant women regarding stunting. The notable improvement between pretest and posttest results highlights the importance of health education as a preventive strategy for stunting.